Asian data privacy laws : trade & human rights perspectives - Greenleaf, G. W. (Graham William) (Oxford : Oxford University Press, 2014)
'Asian Data Privacy Laws' analyses data privacy laws across Asia. Written by the leading expert in this area, the book sets out the international context of the development of national data privacy law before examining and comparing data privacy in 14 Asian countries.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 4, 2014).
Keywords: Data protection -- Law and legislation -- Asia